An Investigation of the Role and Effectiveness of Research-led Teaching in Higher Education - Singh, Deler; Kaur, Gurvinder (International Journal of Psychosocial Rehabilitation, 2020)
The paper studies the role of research led teaching in higher education. The research has been conducted amongst the first year engineering undergraduate students with an aim to initiate the minto the realm of scientific and scholarly research. This would prepare them to design projects at later stages in their degree. An activity on technical report writing was revised to familiarise the students with academic readings. The students were made to look for academic literature on the topics assigned and come up with summaries of the articles. The specific topics were chosen based on these summaries. Surveys were conducted by the students which were later compiled into reports. This activity ensured that the students were better equipped to conduct research before going in for projects in their respective streams of engineering. The case drew upon various theories and models to explain the need to change from ‘teaching based research’ to ‘research-based teaching’.